Effect of salted fish waste and cow manure on NPK availability and uptake of lowland rice on peat soil in Pelalawan Riau - Dian Syafitri Ompusunggu; Benito Heru Purwanto; Cahyo Wulandari; Sri Nuryani Hidayah Utami (Jurnal Ilmu Pertanian, 2020)
The low yield of rice in thick peat can be overcome by provisioning complete nutrients. Various efforts have been made to increase the productivity of Indonesian peatlands, one of which is by adding salted fish waste and cow manure. This research was carried out on a plastic house scale from October 2017 to January 15, 2018, in Pelalawan District, Pelalawan Regency, Riau. This research was arranged in a Completely Randomized Design (CRD), consisting of eight treatments, namely L0 = Control, L1 = 1.5 ton.ha-1 of fish waste, L2 = 2.25 ton.ha-1 of fish waste, L3 = 7 tons/ha of cow manure, L4 = 15 ton.ha-1 of cow manure, L5 = 1.5 ton.ha-1 of fish waste + 7 ton.ha-1 of cow manure, L6 = 1.5 ton.ha-1 of fish waste + 15 ton.ha-1 of cow manure, L7 = 2. 25 ton.ha-1 of fish waste + 7 ton.ha-1 of cow manure, and L8 = 2.25 ton.ha-1 of fish waste + 15 ton.ha-1 of cow manure. The results showed that the application of cow manure and salted fish waste could increase soil pH, total NPK, and NPK uptake. The application of 2.25 tons/ha of fish waste and 15 tons/ha of cow manure resulted the best results in soil pH, total NPK, and NPK uptake, therefore it is recommended for the cultivation of lowland rice on peat soil.